Use of Peer Observation for Self-enhancement - Adhikari, Bal Ram (Journal of NELTA Gandaki, 2019)
The present article concerns the use of peer observation, particularly in the context of microteaching, for self-enhancement. The study followed a mixed methods design comprising survey and focused discussion. The data were collected from prospective external evaluators of teaching practice who participated in the training session entitled Find Good Practices of Teaching Demonstrated by their Peers and Adopt and Adapt According to their Needs so as to find out the participants' perspectives on observing their peers' classes and benefits they reaped from the observation. Analysis of the participants' written and oral accounts reveals that peer observation is a rewarding learning experience; and observation is likely to be fruitful when it is preceded by self-inquiry, that is, identification of what the observer himself/herself is lacking and followed by critical reflection on the observed lesson and the observer's own practice. Also, the peer's weaknesses can be employed as a critical incident to question one's own teaching behavior.